Estimating the effect of teacher pay on pupil attainment using boundary discontinuities - Ellen Greaves; Luke Sibieta (Institute for Fiscal Studies (IFS), 2014)
This paper provides causal estimates of the effect of teacher pay on pupil attainment using a sharp geographical discontinuity in teacher salaries. We compare schools in close proximity to a pay zone boundary to estimate the effect of teacher salary differentials on pupil attainment. We find that these differences in salary scales do translate into differences into actual teacher pay levels. However, we find little evidence that higher teacher salary scales increases pupil attainment in national assessments at age 11, and are able to rule out quantitatively small effects of 0.07 and 0.02 standard deviations in English and maths, respectively. These results imply that variations in teacher pay of the magnitude we observe (around 5%) are unlikely to be effective for attracting and retaining higher quality teachers.
Keywords: 330